Peptic Ulcer Disease among Patients Undergoing Upper Gastrointestinal Endoscopy in a Tertiary Care Centre: A Retrospective Study (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Peptic Ulcer is one of the common disease in developing nations including Nepal. Upper Gastrointestinal Endoscopy is gold standard for establishing the diagnosis. There are limited studies providing epidemiological data of Peptic ulcer in our country. The aim of this study is to investigate the prevalence of peptic ulcer disease in patient who came for upper gastrointestinal endoscopy at Gorkha Public Hospital Ghorahai, Dang.Materials and Methods: It is a retrospective observational study among adults presenting with Gastrointestinal symptoms and undergoing upper Gastrointestinal Endoscopy at Gorkha Public Hospital Pvt. Ltd, Ghorahi, Dang between May 2013-Dec 2022. Data were extracted from hospital computer records and analysed.Results: Results: A total of 2897 with age ranging from 8 years to 78 years patient undergoing Upper Gastrointestinal (UGI) endoscopy were evaluated. Among them, 168 had Peptic Ulcer (87 had Gastric ulcer (3%) and 81 had Duodenal Ulcer (2.79%)) and 1321 had non erosive gastritis/ duodenitis. Peptic ulcer was found to be more common in middle age ranging from 40-59 years of age, N=75 (44.64%0. There was male predominance in prevalence, N= 98 (58.33%).Conclusions: Conclusion: Peptic Ulcer is fairly common in our part of the world with limited data available in our country. The overall incidence is high in middle age. Although, our study showed slight male predominance in prevalence, the disease is common in both gender. This is single center study and results cannot be generalized and needs further multicentric and community-based studies.